Triplication in permanent teeth: A rare case report - Gera, Nidhi (J Oral Maxillofac Pathol, 2017)
Fusion is an anomaly manifested in both deciduous and permanent dentitions. Triple tooth refers to the union of three separate tooth entities. It can involve the normal dentition or supernumerary teeth. Triplication is rarely encountered in deciduous and permanent dentition with an incidence of 0.02%. The case presented herein describes a rare case of triplication in permanent maxillary incisors and supernumerary teeth in a 15-year-old female.